Oral health at a Peruvian police academy - Christian Renzo Aquino Canchari; Katia Medalith Huamán-Castillon (Editorial Ciencias Médicas, 2020)
Introduction: The oral health of young adults is a basic human right, and its contribution is fundamental for the enjoyment of a good quality of life. Objective: Determine oral health at a Peruvian police academy from July to August 2017. Methods: An observational descriptive cross-sectional study was conducted. The sample was 276 young adults randomly selected according to inclusion and exclusion criteria and in compliance with the ethical standards of scientific research. Oral health was evaluated with the aid of an epidemiological card containing the following indicators: CPOD index, dental caries significance (DCS) index, simplified oral hygiene index (OHI-S), and WHO dental prosthesis need and situation. The evaluation was conducted by a qualified observer under natural light. Data were processed with the software STATA v 14, using frequency distribution tables and figures. Results: Dental caries prevalence was 63.76% (CPOD= 3.86; DCS= 9.64), OHI-S: 2.02 (SD= 0.41). Fixed partial dentures were the most commonly used, and they were required in both jaws. Conclusions: Dental caries experience was moderate, oral hygiene status was fair, and fixed partial dentures were the most commonly required for both jaws. Although the indicators are heartening, there is still an urgent need to implement oral health policies in the police community.